The Hajj 2019 Vaccine Requirements and Possible New Challenges - Jaffar A. Al-Tawfiq; Ziad A. Memish
Each year millions of pilgrims perform the annual Hajj from more than 180 countries around the world. This is one of the largest mass gathering events and may result in the occurrence and spread of infectious diseases. As such, there are mandatory vaccinations for the pilgrims such as meningococcal vaccines. The 2019 annual Hajj will take place during August 8-13, 2019. Thus, we review the recommended and mandated vaccinations for the 2019 Hajj and Umrah. The mandatory vaccines required to secure the visa include the quadrivalent meningococcal vaccine for all pilgrims, while yellow fever, and poliomyelitis vaccines are required for pilgrims coming from countries endemic or with disease activity. The recommended vaccines are influenza, pneumococcal, in addition to full compliance with basic vaccines for all pilgrims against diphtheria, tetanus, pertussis, polio, measles, and mumps. It is imperative to continue surveillance for the spread of antimicrobial resistance and occurrence of all infectious diseases causing outbreaks across the globe in the last year, like Zika virus, MDR-Typhoid, Nipah, Ebola, cholera, chikungunya and Middle East Respiratory Syndrome Coronavirus.